GenoMiner: a tool for genome-wide search of coding and non-coding conserved sequence tags - Castrignanò, Tiziana; De Meo, Paolo D'Onorio; Grillo, Giorgio; Liuni, Sabino; Mignone, Flavio; Talamo, Ivano Giuseppe; Pesole, Graziano (Bioinformatics, 2006)
GenoMiner is a software tool that searches for regions of similarity between user-submitted genome or transcript sequences and user-specified whole genome assemblies. The program then identifies conserved sequence tags (CSTs) in these homologous regions and provides a prediction of their coding or non-coding nature. The analysis is carried out through three steps: (1) definition of sequence regions homologous to the query sequence in the selected target genomes by a fast BLAT alignment; (2) identification of CSTs by a more sensitive BLAST-like alignment between the query and the homologous regions in the target genomes and (3) assessment of the coding or non-coding nature of detected CSTs through the computation of a suitable coding potential score. GenoMiner allows the user to search the query sequence against a number of vertebrate genome assemblies in a single run providing a user-friendly graphical output. Availability: . GenoMiner software and documentation is available from the authors upon request. Contact: graziano.pesole@unimi.it